Physical properties of PHA 2014 JO25 from a worldwide observational campaign. Issue 4 (3rd December 2018) - Aznar, Amadeo; de León, J; Popescu, M; Serra-Ricart, M; Short, P; Pravec, P; Vaduvescu, O; Licandro, J; Ortiz, J L; Sota, A; Morales, N; Lorenzi, V; et al.
ABSTRACT: The study of minor planets is motivated both by fundamental science of Solar system origins (some of these bodies contain the most pristine materials from the early ages of the planetary nebula) and by practical reasons concerning space exploration and impact frequency with Earth. Among minor bodies, near-Earth asteroids are a particularly important group: these objects are nearby the Earth's orbit and they represent both resources and hazards to humans. This is the case of 2014 JO25 . The encounter of this potentially hazardous asteroid with the Earth at 0.011 75 au on 2017 April 19 was a good opportunity to study its properties through photometric and spectral analyses. The work we present here has been carried out thanks to a worldwide observational campaign that included time-series photometry and spectroscopy in the visible and near-infrared wavelengths. The optical images for photometric analysis were collected at different phase angles using small telescopes (<0.5 m) and medium telescopes (from 0.6 to 1.5 m). Spectral analysis was performed by 2–4 m telescopes. The light curve of 2014 JO25 indicates a synodic rotational period of 4.5286 ± 0.0004 h. Although rotational period had been previously obtained by other authors, this work confirms it with a better accuracy. The obtained reflectance spectrum of this asteroid indicates that it belongs to the S-complex and its surface is most likely composed of a mixture of pyroxenes and olivine. From the comparison of its spectrum to those of meteorite samples, as well as from the wavelength position of the first absorption band (close to 0.9$μ$ m), we suggest that this asteroid might contain a large fraction of low-calcium pyroxene and, tentatively, some amounts of metal.